Enuresis and nocturia in children with sickle cell disease - Berkel, İzzet; Ergene, Turhan (The Turkish Journal of Pediatrics, 1968)
The parents of 26 patients over four years of age with SCD were interviewed directly or through questionnaires to determine the incidence of enuresis and/or nocturia. Of this group, 34.6 per cent had enuresis while only 16.7 per cent of the control group registered this complaint. The incidence of hyposthenuria with enuresis and/or nocturia among these 26 patients was 69.2 per cent. Their parents and siblings also presented a high incidence of nocturia and enuresis.